Making Sense in and of the Asexual Community: Navigating Relationships and Identities in a Context of Resistance. (30th June 2014) - Chasin, CJ DeLuzio
Abstract: Despite some increased visibility in recent years, the asexual community and asexuality generally remain largely unknown. Aiming to demystify asexuality, this paper discusses the context of anti‐asexual animosity in which the (largely American) asexual community is situated. Specifically, the asexual community constructed itself in response to hostility, including explicit anti‐asexual discrimination, homophobia against asexual people perceived to be lesbian or gay, and the negative impact of (implicit) pathologising low sexual desire. This theoretical paper outlines some of the unique challenges asexual people face negotiating identities and relationships; the collective sense‐making strategies they use (generating language and discourse) to do so; and why these things are central to understanding asexual people's experiences. This is accomplished through a purposeful review of literature and a case study of the Asexual Visibility and Education Network as an asexual community space. Understanding the challenges asexual people face and the resources they invoke to overcome them helps applied psychologists develop the cultural competence they need to work effectively with the asexual people they will encounter. Copyright © 2014 John Wiley & Sons, Ltd.